Study of functional outcome of minimal invasive spine surgery through tubular microdiscectomy with laminotomy in case of single level prolapsed lumbar intervertebral disc - Sidhdhapuria, Pratik; Pathak, Arjun; Rathod, Jay; Rakholiya, Pratik (International Journal of Research in Orthopaedics, 2026)
Background: Lumbar disc herniation (LDH) is one of the most common causes of low back pain and radiculopathy. Traditional open discectomy has been effective but is associated with greater tissue disruption, postoperative pain, and longer recovery. Minimally invasive spine surgery (MISS), particularly tubular microdiscectomy with laminotomy, aims to achieve adequate neural decompression while minimizing approach-related morbidity. Aim was to evaluate the functional outcomes of patients undergoing tubular microdiscectomy with laminotomy for single-level prolapsed lumbar intervertebral disc (PLID). Methods: This prospective observational study was conducted at the Department of Orthopaedics, SMIMER, Surat, from February 2023 to October 2024, involving 25 patients aged 20-70 years with single-level PLID unresponsive to ≥6 months of conservative treatment. All patients underwent tubular microdiscectomy with laminotomy. Clinical assessment included VAS (Visual analogue scale) for pain and ODI (Oswestry disability index) for functional disability. Follow-ups were performed at 6 weeks, 3 months, and 6 months postoperatively. Radiological evaluation confirmed adequate decompression. Compliance rate was 100%. Results: All patients demonstrated significant postoperative improvement. VAS scores showed progressive reduction in back and leg pain across all follow-up intervals. ODI scores improved markedly, indicating enhanced functional capacity and return to activities of daily living. No major complications, infections, or neurological deterioration were noted. Recovery was rapid, with most patients regaining independent ambulation within days. Cosmetic results and patient satisfaction were high, consistent with the benefits of minimally invasive techniques. Conclusions: Tubular microdiscectomy with laminotomy is an effective and safe minimally invasive procedure for managing single-level PLID. It offers excellent pain relief, improved functional outcomes, shorter hospital stay, and minimal postoperative morbidity. This technique serves as a reliable alternative to conventional open surgery, particularly in appropriately selected patients.